Selected Papers from ASEPFPM2015 (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This Special Issue cooperates with the 5th Asian Symposium on Emulsion Polymerization and Functional Polymeric Microspheres (ASEPFPM 2015) (http://asepfpm5.csp.escience.cn). Polymeric microspheres are basic materials for recent progress in environmental science, architecture, biomedicine, electronics, food, cosmetics, etc. While much progress has been made over the past few decades, there are still big challenges for the preparation of functional particles and the verification of preparation mechanisms; there is much room for growth in our ability to provide for high performance in these areas. The general theme of this symposium is to discuss recent advances in both fundamentals and applications, as well as to promote science and industrialization translation.